A Anti-Vibrio Activity of Bacteria Isolated from the Intestine of Mantis Shrimp (Harpiosquilla sp.): Aktivitas Anti-Vibrio Bakteri yang Diisolasi dari Usus Udang Mantis (Harpiosquilla sp.) - Navita Desy Ratnaningsih; Petrus Hary Tjahja Soedibya; Jefri Anjaini (Journal Of Artha Biological Engineering, 2026)
Shrimp diseases caused by Vibrio spp. remain a major constraint in aquaculture, necessitating the exploration of alternative antibacterial agents from natural sources. This study aimed to determine the proportion and antibacterial activity of bacterial isolates derived from the intestines of mantis shrimp. Samples were collected from Jepara, Pemalang, and Cilacap waters using a purposive sampling approach. The research methods included bacterial isolation, morphological characterization, and screening of antivibrio activity. Antibacterial activity was evaluated against Vibrio parahaemolyticus, Vibrio alginolyticus, and Vibrio harveyi using dotting and disc diffusion methods. The results showed that 27% of isolates from Jepara, 44% from Pemalang, and 16% from Cilacap exhibited antivibrio activity. The inhibition zones ranged from 1.1–11.0 mm against V. parahaemolyticus, 3.3–9.0 mm against V. alginolyticus, and 2.2–11.8 mm against V. harveyi. These findings indicate that intestinal bacteria of mantis shrimp from all sampling locations possess antibacterial activity against Vibrio spp., highlighting their potential as promising candidates for the development of biocontrol agents in sustainable aquaculture systems.